Mathematical modelling of MHD hybrid nanofluid flow in a convergent and divergent channel under variable thermal conductivity effect - Alharbi Abdulaziz H. (Applied Rheology)
The aim of this research is to analyse the combined effect of variable thermal conductivity and nonlinear thermal radiation on magnetohydrodynamic (MHD) hybrid nanofluid flow in convergent-divergent channels. The effects of two nanoparticles (i.e. ZrO2{\text{ZrO}}_{\text{2}} and SiO2{\text{SiO}}_{\text{2}}) in base fluid (i.e. H2O{\text{H}}_{\text{2}}\text{O}) are considered in this work. The partial differential equations modelling the problem are reduced to ordinary differential equations following the application of the similarity transformations. The system has been solved analytically with the differential transform method and numerically with the Runge–Kutta–Fehlberg 4th–5th order method with the assistance of the shooting technique. Comprehensive analysis and discussion have been conducted regarding the impact of multiple governing parameters on the dimensionless velocity and temperature distributions. These parameters include variable thermal conductivity, nonlinear thermal radiation, Hartman number, and hybrid nanoparticle volume fraction. Finally, this method will provide some insights into the usefulness of MHD hybrid nanofluid flow in convergent-divergent channels, and the results produced by the analytical data have also been strengthened and verified by the use of numerical data as well as data from the literature.